2004
DOI: 10.1002/hep.20015
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of rat hepatic stellate phenotype by natural and synthetic retinoids

Abstract: Activation of hepatic stellate cells (HSC) is a central event in the pathogenesis of liver fibrosis during chronic liver injury. We examined the expression of retinoic acid (RAR) and retinoid X receptors (RXR) during HSC activation and evaluated the influence of natural and synthetic retinoic acids (RA) on the phenotype of culture-activated HSC. The expression of the major RAR/RXR subtypes and isoforms was analyzed by Northern hybridization. Presence of functional receptor proteins was established by gel shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 58 publications
7
88
0
7
Order By: Relevance
“…Although loss of retinoid is a prominent feature accompanying stellate cell activation both in vivo (421) and in culture (175), it is unknown whether this process is a prerequisite for activation to occur. The reports about effects of retinoids on stellate cells and fibrogenesis are contradictory (115,116,199,236,423,460,461,563,582,583,588). In culture, both retinol and retinoic acid suppress stellate cell proliferation, and retinoic acid (RA) is 1,000 times more potent than retinol (116).…”
Section: Effects Of Retinoids On Stellate Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although loss of retinoid is a prominent feature accompanying stellate cell activation both in vivo (421) and in culture (175), it is unknown whether this process is a prerequisite for activation to occur. The reports about effects of retinoids on stellate cells and fibrogenesis are contradictory (115,116,199,236,423,460,461,563,582,583,588). In culture, both retinol and retinoic acid suppress stellate cell proliferation, and retinoic acid (RA) is 1,000 times more potent than retinol (116).…”
Section: Effects Of Retinoids On Stellate Cellsmentioning
confidence: 99%
“…More recently, divergent effects of all-trans-RA and 9-cis-RA on stellate cells have been observed (234). There are also different effects between natural and synthetic retinoids (236).…”
Section: Effects Of Retinoids On Stellate Cellsmentioning
confidence: 99%
“…Activated HSCs respond to exogenous retinoids in culture (Hellemans et al 2004;Martucci et al 2004;Vogel et al 2000). Studies have shown that supplementation of cultured HSCs with ATROH prevents the activation of HSCs, inhibits transdifferentiation, and promotes the lipofibroblastic vitamin-A-storing phenotype (Vogel et al 2000;Fortuna et al 2003;Hellemans et al 2004).…”
Section: Introductionmentioning
confidence: 96%
“…In liver, it attenuated ischemia/reperfusion liver injury, suppressing the inflammatory signals via increased IκBα and repressed NF-κB p65 expression [152] . In addition, the activation of RXR and RAR in hepatic stellate cells may attenuate their activation and proliferation [153] , subsequently ameliorating carbon tetrachloride-induced liver fibrosis in vivo [154][155][156][157] . Furthermore, ATRA treatment repressed CYP7A1 promotor activity [158] .…”
Section: Bile Acids Receptors and Other (Nuclear Hormone) Receptorsmentioning
confidence: 99%